1989
DOI: 10.1002/1098-108x(198905)8:3<285::aid-eat2260080304>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pregnancy on anorexia nervosa and bulimia

Abstract: The present study examines the impact of pregnancy on anorexia nervosa and bulimia. A survey of women with an active eating disorder involving anorexia nervosa, bulimia, or mixed symptoms 6 months prior to their first pregnancy was undertaken to gain information on attitudes toward becoming pregnancy, fears and concerns related to the unborn child, the impact on eating disorder behaviors prenatal and postnatal, weight gain and weight gain of the baby as an indicator of its health, and the obstetricians view of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
92
2
4

Year Published

1991
1991
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(102 citation statements)
references
References 9 publications
4
92
2
4
Order By: Relevance
“…Estudos demonstraram que a gravidez pode, por um lado, agravar, manter, reduzir, despoletar recaídas, ou mesmo evitar comportamentos de risco em mulheres com história passada ou actual de perturbações do comportamento alimentar, ou precipitar ou manter afastadas destes comportamentos as mulheres sem sintomatologia (Blais et al, 2000;Crow, Agras, Crosby, Halmi, & Mitchell, 2008;Crow, Keel, Thuras, & Mitchell, 2004;Dunker, Alvarenga, & Alves, 2009;Edelstein, 2007;Hollifield & Hobdy, 1990;Lemberg & Phillips, 1989;Mitchell-Gieleghem et al, 2002;Newton & Chizawsky, 2006;Ramchandani & Whedon, 1988), podendo estas alterações ser permanentes ou transitórias (Blais et al, 2000;Newton & Chizawsky, 2006). Siega-Riz et al (2008) constataram que as mulheres com bulimia nervosa antes e durante a gravidez exibiam padrões dietéticos diferentes das grávidas sem perturbações do comportamento alimentar.…”
Section: Perturbações Do Comportamento Alimentar E Gravidezunclassified
See 2 more Smart Citations
“…Estudos demonstraram que a gravidez pode, por um lado, agravar, manter, reduzir, despoletar recaídas, ou mesmo evitar comportamentos de risco em mulheres com história passada ou actual de perturbações do comportamento alimentar, ou precipitar ou manter afastadas destes comportamentos as mulheres sem sintomatologia (Blais et al, 2000;Crow, Agras, Crosby, Halmi, & Mitchell, 2008;Crow, Keel, Thuras, & Mitchell, 2004;Dunker, Alvarenga, & Alves, 2009;Edelstein, 2007;Hollifield & Hobdy, 1990;Lemberg & Phillips, 1989;Mitchell-Gieleghem et al, 2002;Newton & Chizawsky, 2006;Ramchandani & Whedon, 1988), podendo estas alterações ser permanentes ou transitórias (Blais et al, 2000;Newton & Chizawsky, 2006). Siega-Riz et al (2008) constataram que as mulheres com bulimia nervosa antes e durante a gravidez exibiam padrões dietéticos diferentes das grávidas sem perturbações do comportamento alimentar.…”
Section: Perturbações Do Comportamento Alimentar E Gravidezunclassified
“…Algumas mulheres pioram ou mesmo recomeçam estes comportamentos (Dunker et al, 2009;Edelstein, 2007;Kouba, Hälström, Lindholm, & Hirschberg, 2005;Newton & Chizawsky, 2006), sendo o principal impulsionador as alterações físicas e psicológicas que advêm da gravidez (Makino, Hashizume, & Tsuboi, 2007), nomeadamente o medo relativo ao aumento de peso (Lemberg & Phillips, 1989). Num estudo de Rand, Willis e Kuldau (1987), este medo surgiu com maior frequência no primeiro trimestre de gravidez e segundo mês do período pós-parto.…”
Section: Perturbações Do Comportamento Alimentar E Gravidezunclassified
See 1 more Smart Citation
“…Symptoms frequently returned after delivery, and in almost half, eating was more disturbed. In another sample of 43 women reporting abnormal eating patterns during the six months before conception, symptomatic improvement occurred during pregnancy in 70%, but 44% retained some symptoms until delivery (Lemberg & Philips, 1989).…”
Section: Weight Gain In Pregnancy and Exacerbation Of Eating Disordersmentioning
confidence: 99%
“…Many patients reported episodes of overeating but only one (who had a previous history of bulimia) had associated feelings of loss of control. Lemberg & Philips (1989) also reported that a fear of losing control of weight during pregnancy is commoner in patients with eating disorders.…”
Section: Weight Gain In Pregnancy and Exacerbation Of Eating Disordersmentioning
confidence: 99%